Target-Site Point Mutation Conferring Resistance to Trifluralin in Rigid Ryegrass (Lolium rigidum). Issue 2 (30th October 2017) - Fleet, Benjamin; Malone, Jenna; Preston, Christopher; Gill, Gurjeet
Abstract : Populations of rigid ryegrass suspected of resistance to trifluralin due to control failures exhibited varying levels of susceptibility to trifluralin, with 15 out of 17 populations deemed resistant (>20% plant survival). Detailed dose–response studies were conducted on one highly resistant field-evolved population (SLR74), one known multiply resistant population (SLR31), and one susceptible population (VLR1). On the basis of the dose required to kill 50% of treated plants (LD50 ), SLR74 had 15-fold greater resistance than VLR1, whereas, the multiply resistant SLR31 had 10-fold greater resistance than VLR1. Similarly, on the basis of dose required to reduce shoot biomass by 50% (GR50 ), SLR74 had 17-fold greater resistance than VLR1, and SLR31 had 8-fold greater resistance than VLR1. Sequencing of the α-tubulin gene from resistant plants of different populations confirmed the presence of a previously known goosegrass mutation causing an amino acid substitution at position 239 from threonine to isoleucine in resistant population SLR74. This mutation was also found in 4 out of 5 individuals in another highly resistant population TR2 and in 3 out of 5 individuals of TR4. An amino acid substitution from valine to phenylalanine at position 202 was also observed in TR4 (3 out of 5 plants) and TR2 (1 out of 5 plants). There was no target-site mutation identified in SLR31. This study documents the first known case of field-evolved target-site resistance to dinitroaniline herbicides in a population of rigid ryegrass.